P128 Contextual approaches to understanding HIV testing and prevention engagement among urban refugee adolescents and youth in Kampala, Uganda - Logie, C.; Okumu, M.; Hakiza, R.; Mwima, S.; Kyambadde, P..; Mbuagbaw, P. (Sex Transm Infect, 2021)
HIV prevention needs are understudied with urban refugee youth. We explored experiences, preferences and engagement with HIV testing and prevention among urban refugee adolescents and youth in Kampala, Uganda, with a focus on the role of contextual factors in shaping access and uptake. This qualitative community-based study with urban refugee youth aged 16–24 living in Kampala’s informal settlements involved five focus groups (FG), including two with women, two with men, and one with sex workers. We also conducted five in-depth key informant interviews. We conducted thematic analysis informed by Campbell and Cornish’s conceptualization of material and symbolic contexts. Refugee youth participants (n=44; mean age: 20.25, SD: 2.19; men: n=17; women: n=27) were from the Democratic Republic of Congo (n=29), Rwanda (n=11), Burundi (n=3), and Sudan (n=1). Participant narratives reflected material, symbolic and relational contexts that shaped HIV testing awareness, preferences and uptake. Material contextual factors that presented barriers to HIV testing and prevention engagement included: transportation costs to clinics, overcrowded living conditions that limited access to private spaces, low literacy, and language barriers. Symbolic contexts that constrained HIV testing engagement included medical mistrust of HIV testing, and inequitable gender norms. Religion emerged as an opportunity to connect with refugee communities and to address conservative religious positions on HIV and sexual health. Relational contexts connected with HIV prevention and testing engagement included linkages with professional support, family, friends, and intimate partners. Many participants suggested the need for mental health support alongside HIV care, particularly for HIV testing. Efforts to increase access and uptake along the HIV testing and prevention cascade can meaningfully engage urban refugee adolescents and youth to develop culturally and contextually relevant services to optimize HIV and sexual health outcomes. Integrated mental health and HIV services may be warranted for urban refugee adolescents and youth.
Keywords: P128 Contextual approaches; HIV testing; urban refugee adolescents and youth